2005
DOI: 10.1021/jm058034a
|View full text |Cite
|
Sign up to set email alerts
|

7-(1,1-Dimethylethyl)-6-(2-ethyl-2H-1,2,4- triazol-3-ylmethoxy)-3-(2-fluorophenyl)- 1,2,4-triazolo[4,3-b]pyridazine:  A Functionally Selective γ-Aminobutyric AcidA(GABAA) α2/α3-Subtype Selective Agonist That Exhibits Potent Anxiolytic Activity but Is Not Sedating in Animal Models

Abstract: There is increasing evidence that compounds with selectivity for gamma-aminobutyric acid(A) (GABA(A)) alpha2- and/or alpha3-subtypes may retain the desirable anxiolytic activity of nonselective benzodiazepines but possess an improved side effect profile. Herein we describe a novel series of GABA(A) alpha2/alpha3 subtype-selective agonists leading to the identification of the development candidate 17, a nonsedating anxiolytic in preclinical animal assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…TPA023 ( Fig. 1) was synthesized as described elsewhere (Carling et al, 2005 This precursor was reduced to the aldehyde and reacted with 3-chloro-4-(1,1-dimethyleth-1-yl)-6-hydrazinopyridazine to produce the imine N-[…”
Section: Methodsmentioning
confidence: 99%
“…TPA023 ( Fig. 1) was synthesized as described elsewhere (Carling et al, 2005 This precursor was reduced to the aldehyde and reacted with 3-chloro-4-(1,1-dimethyleth-1-yl)-6-hydrazinopyridazine to produce the imine N-[…”
Section: Methodsmentioning
confidence: 99%
“…Carling et al investigated that there is increasing evidence that compounds (45) with selectivity for gamma-aminobutyric acid-A (GABA-A) alpha2-and/ or alpha3-subtypes may retain the desirable anxiolytic activity of nonselective benzodiazepines but possess an improved side effect profile. In this study, they have described a novel series of GABA-A alpha2/alpha3 subtype-selective agonists leading to the identification of the non-sedating anxiolytic agents in preclinical animal assays [118]. …”
Section: Antianxiety Activitymentioning
confidence: 99%
“…TPA023 (Atack et al, 2006) andTPA123 (TP13, McCabe et al, 2004;MRK-067, Atack, 2009) were synthesized as described by Carling et al (2005), where they were identified as compounds 17 and 15, respectively). For intravenous administration, they first were dissolved in polyethylene glycol 400, which then was diluted 50% with 0.9% sterile saline.…”
Section: Drugsmentioning
confidence: 99%